2018
DOI: 10.1016/j.jiph.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and microbiological profile comparison between community and hospital acquired infections: A multicenter retrospective study in Lebanon

Abstract: Our results confirm that hospital acquired infections/bacteria have higher rates of resistance when compared to community acquired; these rates increase with age, immunosuppression and are inversely proportional with COPD. Therefore, physicians should be aware of patients' comorbidities to properly guide initial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
3
24
1
2
Order By: Relevance
“…The present study showed that K pneumoniae isolates were recovered from 42/250 (16.8%) of HAI cases. Similar findings were reported by other researchers . Our strains were recovered from different age groups at nearly the same percentage with the exception of patients <10 years old, where the percentage was much higher (55.9%) and patients >50 years with percentage (27.8%).…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that K pneumoniae isolates were recovered from 42/250 (16.8%) of HAI cases. Similar findings were reported by other researchers . Our strains were recovered from different age groups at nearly the same percentage with the exception of patients <10 years old, where the percentage was much higher (55.9%) and patients >50 years with percentage (27.8%).…”
Section: Discussionsupporting
confidence: 91%
“…In general, it has been shown that the ecological differences in each geographic region can determine the phylogenetic groups involved in UTIs in each region (20). For example, most studies in France and America have reported that most commensal specimens are related to groups A and B1 (24,25) while in this study, they mostly belonged to groups B2 and A. This difference in each region can be affected by antibiotics usage or host genetic factors.…”
Section: Discussionmentioning
confidence: 62%
“…That would probably explain why in this study, the percentage of E. coli isolates in men was noticeably higher in group D than in other phylo-groups. Moreover, it has been established so far that the pathogens causing community-acquired infections are less antibiotic resistant than the ones responsible for nosocomial infections, and vice versa (23,24). Therefore, it would be reasonable to assume that group D might be more virulent than other phylo-groups.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a common cause of community-acquired and nosocomial acquired pneumonia and is responsible for 10% of all hospital-acquired infections worldwide (MATTA et al, 2018). The development of resistance of P. aeruginosa to antibiotics is increasing globally due to the overuse of antibiotics (YAYAN et al, 2015).…”
Section: Mechanisms Of Resistence To Antimicrobial Agents In Differenmentioning
confidence: 99%